Peran Kelompok Tani Cibeusi Subur dalam Pemberdayaan Masyarakat Melalui Program Pelatihan Pertanian - Muhammad Farhan Agustian; Saeful Anwar; Ratna Dewi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This paper aims to analyze the role of fertile Cibeusi Subur farmer groups in community through agricultural training programs, the discussion was directed an answering problems relatad to the program, implementation and results achieved. The research use dercriptive method with a qualitative approach. Data collection technique used observation, interviews, and documentation studies.Qualitative data analysis that is precisely and profoundly trough the interpretation of logic that is linked to the context of Islamic community empeworment. The results of the study showed that the program of the farmers group was fertile in empowering the community through agricultural training programs is individual and group training, individual training includes processing of crops and management of fish cultivation while group training is in the form of fertilizer and management, the process of implementing agricultural training consists several stages namely the planning phase, the implementation phase and evaluation phase and the results of empowerment are among others the emergence of public awareness in managing agricultural potential; Increased income of people from the agricultural sector. In general, it can be concluded that community empowerment by the Cibeusi Subur farmer group through the agricultural training program was quite successful despite many obstacles. These activities are able to change the mindset of the community and increase the lifestyle of the people to be better and more empowered.